Recommendations for a Successful Implementation of Guided Pathways Model in North Carolina Community Colleges - Somanita Kheang; Sarah Deal; Keith Street Robinson (Adult Education Research Conference, 2022)
This research aims to study challenges of implementing Guided Pathways model in 17 North Carolina community colleges. The findings indicated that most colleges struggled with implementing programs for student success.
Keywords: guided pathways; early implementation; North Carolina; community colleges